2021
DOI: 10.1088/1755-1315/842/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Society 5.0: Green Logistics Consciousness in Enlightening Environmental and Social Sustainability

Abstract: Currently, there is growing attention towards improving sustainability, including the worldwide agenda in moving towards Society 5.0. Since the formulation of Sustainable Development Goals (SDGs), the green logistics issue has been widely recognized as one crucial element to reducing environmental and social impact. Nevertheless, only a few studies in this area were established since the ignorance regarding this issue was immense globally, including in the Malaysian context. This paper intends to examine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…To sum up, the research findings found that environmental advertisements, environmental knowledge and environmental concerns directly and positively influence the predilection for green marketing practices. These findings were consistent with many prior literatures [e.g., 9,10,11,12,13,14,15,16,17,18,19,20,25].…”
Section: Hypothesis Testing: Multiple Linear Regression Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…To sum up, the research findings found that environmental advertisements, environmental knowledge and environmental concerns directly and positively influence the predilection for green marketing practices. These findings were consistent with many prior literatures [e.g., 9,10,11,12,13,14,15,16,17,18,19,20,25].…”
Section: Hypothesis Testing: Multiple Linear Regression Analysissupporting
confidence: 93%
“…Besides that, the Malaysian Government correspondingly demonstrated highly commitment to execute SDGs. Notably, the problem of sustainability already entered core point with the completion of Practice 4.0 as currently updated by the Malaysian Code of Corporate Governance 2021 (MCCG 2021) [25]. Referring to Malaysia's proactive action in encouraging green growth policy and sustainability, the Malaysian government have endorsed the 12th Malaysia Plan that nearly aligned the national growth importance to the SDGs 2030 Agenda.…”
Section: Hypothesis Testing: Multiple Linear Regression Analysismentioning
confidence: 99%
“…Many issues must be addressed when implementing green logistics, but ultimately, when resolved, this can bring cost reductions and, therefore, better efficiency of distribution logistics and increase the quality of services provided to endusers and consumers. In addition, green logistics contributes to logistics companies by reducing material purchase costs, energy costs, waste treatment, and disposal fees to eliminate environmental damage (Sidek et al, 2021). The concept of green logistics can be described as a system of measures designed according to human needs and interests; it emphasizes the strategic direction of implementing sustainable development, considering environmental, economic, social, and humanitarian aspects (Gnann et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This practice reveals an increase in the volume of goods delivered on time, a better use of capacity, promotes the quality of products or services, increases product variety and reduces waste. In addition, the implementation of green logistics benefits organisations by reducing material purchase costs, energy costs, waste treatment and disposal fees in an effort to eliminate environmental damage (Sidek et al, 2021). According to Dzwigol et al (2021) the main principles of green logistics should be: application of an integrated approach in managing logistics flows; rational use of resources; minimum raw materials and packaging, the use of non-recyclables; maximum use of production waste, containers and packaging as secondary raw materials or their environmentally friendly disposal; environmental education and personnel responsibilities increase; implementation of innovative technologies in order to reduce the burden on the environment.…”
Section: Introductionmentioning
confidence: 99%